EKSPRESIVNOST KOT BESEDOTVORNA PRVINA: (na primerih slovekskih glagolov) (Филолошки студии, 2019)
In our discussion expressiveness is limited to word formation and semantic change in Slovenian verbs, marked with a word-formational and semantic deviation from the neutral verbal form. In terms of scope and dissemination the most frequent, as would be expected, are the expressively formed verbs which express states, phenomena and human-related acts, since the basic prerequisite for expression is emotion; most of these are modification derivatives of verbs such as zvončkljati, davkovati, telefonariti etc. There has been an increase also in the use of ordinary verbal derivatives of nouns with expressive nouns, e.g. fotkati, koketkati, kuhariti, martinčkati se, šminkirati, paničariti, pipniti etc., which are typical of colloquial Slovenian, yet as stylistic features make part also of the written language. There is also a number of compounds derived from prepositional phrases such as ufilmiti, udružbiti, vprogramirati etc. Due to language economy one-word Slovenian counterparts like prenašati for downloadati can get established relatively quickly; at the same time having just phrasal translations leads to the use of borrowed expression such as bodibildati ‘to build, develop one’s body’ and velnes ‘feeling well’. At any rate the more recent derivatives of verbs such as cestniniti, fenati, klikati, mejlati, glisirati, hekati, kofetkati, lisičiti, paničariti, parčkati (se), piknikirati, pipsati, repati, rejvati, soteskati, šminkirati, šopingirati, televizirati (se), trimati, ufilmiti, vkodirati reduce and simplify the field of valency by maintaining subject valency only (i.e. monovalent verbs), or at best also includes accusative valency (i.e. divalent verbs).